The effects of leadership style, organizational culture and self-concept on trainers’ performance at the vocational training institutions - Kifta, Decky Antony; Islami, Syaiful; Jalinus, Nizwardi; Abdullah, Rijal (Universitas Negeri Padang, 2022)
The purpose of this study is to understand the influence between leadership style, organizational culture, and self-concept on the trainers’ performance at the Vocational Training Institutions in Batam. These factors are contributing a lot to the successive performance of the students, trainers, and institutions. However, this study only gives framework to the performance of the trainers. Improving trainers’ performance will lead to the improvement of training or educational operation. Some methods such as interviews, observations and questionnaires were used to collect the data. There were 82 trainers selected as respondents to fill the questionnaires, and the data obtained were analyzed using SPSS program. Statistical test methods such as prerequisite analytical tests, t-test, F-test, multiple linear regressions, and coefficients determination. The results give conclusion that there is significant effect and correlation between the leadership styles, organizational cultures, and self-concept on the trainers’ performance at the Vocational Training Institutions in Batam.